Children's Construction Task Performance and Spatial Ability: Controlling Task Complexity and Predicting Mathematics Performance. Issue 3 (December 2014) - Richardson, Miles; Hunt, Thomas E.; Richardson, Cassandra
This paper presents a methodology to control construction task complexity and examined the relationships between construction performance and spatial and mathematical abilities in children. The study included three groups of children ( N =96); ages 7–8, 10–11, and 13–14 years. Each group constructed seven pre-specified objects. The study replicated and extended previous findings that indicated that the extent of component symmetry and variety, and the number of components for each object and available for selection, significantly predicted construction task difficulty. Results showed that this methodology is a valid and reliable technique for assessing and predicting construction play task difficulty. Furthermore, construction play performance predicted mathematical attainment independently of spatial ability.